Barriers to a healthy lifestyle post gestational-diabetes: An Australian qualitative study. Issue 4 (August 2017) - Zulfiqar, Tehzeeb; Lithander, Fiona E.; Banwell, Cathy; Young, Rosemary; Boisseau, Lynelle; Ingle, Martha; Nolan, Christopher J.
Abstract: Background: Overseas-born-women from certain ethnicities are at high risk of type-2 diabetes and related metabolic disorders. This study explored the barriers and facilitators to long-term healthy lifestyle recommendations among Australian-born and overseas-born-women who attended health promotion sessions at a tertiary Australian Hospital for gestational diabetes 3–4 years previously. Method: Face-to-face semi-structured interviews were conducted. Data were analyzed to identify major themes and the differing experiences of both groups of women. Findings: Women in both groups faced many barriers to improve post-gestational-diabetes lifestyle. Women from both groups recalled healthy lifestyle recommendations for during pregnancy they received at the service, but had difficulty recalling the long-term lifestyle recommendations. Timing of the health information, non-reiteration of lifestyle recommendations, uncoordinated and fragmented health system support after childbirth were barriers faced by all women. Additional barriers for overseas-born women included the cultural competence of the health education material, their cultural preferences for food and physical activities and unsupportive family and partner. Both groups had excellent compliance with the first annual postnatal oral-glucose-tolerance-test. This was attributed to the personal motivation and health professional reminder. Women only reverted to the healthy lifestyles postnatally for weight loss. Conclusion: A better understanding of the barriers to healthy lifestyle by women in their everyday lives will assist in the development of culturally appropriate health promotion guidelines and strategies. Constant un-fragmented postnatal engagement by the specialised diabetes clinics and primary health care services is crucial to sustain the healthy lifestyle in the long-term for women with previous gestational-diabetes.